Bibliometric analysis of AI-driven FinTech revolution: mapping global trends, thematic evolution, and future directions - Magli, Amirah Shazana; Sabri, Mohamad Fazli; Hazudin, Siti Fahazarina; Law, Siong Hook; Janani, M.; Najam, Usama; Shahabudin, Sharifah Muhairah (Universiti Putra Malaysia, 2026)
The introduction of Artificial Intelligence (AI) to Financial Technology (FinTech) has revolutionised financial services by reshaping digital banking, risk assessment, and financial decision-making. This paper presents a bibliometric review of the intellectual landscape, thematic development, and academic influence of AI-based FinTech research published between 2012 and 2025. Using the PRISMA methodology, 978 articles from the Web of Science (WoS) database were analysed to identify research trends, collaboration patterns, and citation networks. Results show an immersive publication growth rate of 26.84, indicating rising academic interest in AI-driven FinTech, with global collaboration accounting for 38.4, as supported by an increase in international co-authorship in areas such as robo-advisory services and fraud detection. A notable surge in this research has occurred since 2021, particularly in the areas of big data analytics, conversational AI, and algorithmic risk management, accelerated by the rapid industry transformation of post COVID-19 pandemic. However, despite such advances, issues related to algorithmic bias, transparency, and cybersecurity risks remain persistent. This study presents a full map of AI-powered FinTech scholarly research, outlining research topics, trends, and perspectives of future research, offering valuable insights for scholars, policymakers, and industry champions to navigate the changing AI landscape of the financial services sector.